2019
DOI: 10.3390/en12060983
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Surfactant Oil Recovery Processes and the Role of Phase Behaviour Parameters

Abstract: Chemical Enhanced Oil Recovery (cEOR) processes comprise a number of techniques whichmodify the rock/fluid properties in order to mobilize the remaining oil. Among these, surfactantflooding is one of the most used and well-known processes; it is mainly used to decrease the interfacialenergy between the phases and thus lowering the residual oil saturation. A novel two-dimensionalflooding simulator is presented for a four-component (water, petroleum, surfactant, salt), two-phase(aqueous, oleous) model in porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…They showed that an increase in partition coefficient results in a decrease in interfacial tension; moreover, it was concluded from their experimental results that the partition coefficient is directly related to the temperature and concentration of surfactant. Furthermore, Druetta and Picchioni [14] highlighted the impact of salinity of brine on the partition coefficient, concluding that for surfactant flooding EOR operation it is important to take account of the salinity of brine. As a consequence of the significant effect of surfactants on altering the interfacial properties, in many previous studies, surfactant flooding has been employed as an EOR technique for carbonate reservoirs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that an increase in partition coefficient results in a decrease in interfacial tension; moreover, it was concluded from their experimental results that the partition coefficient is directly related to the temperature and concentration of surfactant. Furthermore, Druetta and Picchioni [14] highlighted the impact of salinity of brine on the partition coefficient, concluding that for surfactant flooding EOR operation it is important to take account of the salinity of brine. As a consequence of the significant effect of surfactants on altering the interfacial properties, in many previous studies, surfactant flooding has been employed as an EOR technique for carbonate reservoirs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%